2022
DOI: 10.1161/hyp.0000000000000217
|View full text |Cite
|
Sign up to set email alerts
|

Revascularization for Renovascular Disease: A Scientific Statement From the American Heart Association

Abstract: Renovascular disease is a major causal factor for secondary hypertension and renal ischemic disease. However, several prospective, randomized trials for atherosclerotic disease failed to demonstrate that renal revascularization is more effective than medical therapy for most patients. These results have greatly reduced the generalized diagnostic workup and use of renal revascularization. Most guidelines and review articles emphasize the limited average improvement and fail to identify those clinical population… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(36 citation statements)
references
References 128 publications
1
35
0
Order By: Relevance
“…Results of several randomized controlled studies have questioned the value of routine revascularization for ARAS, since the latter was not associated with improved cardiovascular outcomes when compared with medical therapy alone. 27 In the ASTRAL (Angioplasty and Stenting for Renal Artery Lesions) trial, comparing medical therapy with stenting for ARAS in randomly assigned 806 patients, there was no difference in the pre -established outcomes of renal function decline, renal events, cardiovascular events, or death. 27,28 Also, in the CORAL (Cardiovascular Outcomes in Renal Atherosclerotic Lesions) trial, which enrolled 931 patients with ARAS, there were no differences in primary outcomes including major cardiovascular events (myocardial infarction, stroke, hospitalization was more frequent than in the patients with primary hypertension.…”
Section: Atherosclerotic Renal Artery Stenosis Renal Revascularizatio...mentioning
confidence: 99%
See 4 more Smart Citations
“…Results of several randomized controlled studies have questioned the value of routine revascularization for ARAS, since the latter was not associated with improved cardiovascular outcomes when compared with medical therapy alone. 27 In the ASTRAL (Angioplasty and Stenting for Renal Artery Lesions) trial, comparing medical therapy with stenting for ARAS in randomly assigned 806 patients, there was no difference in the pre -established outcomes of renal function decline, renal events, cardiovascular events, or death. 27,28 Also, in the CORAL (Cardiovascular Outcomes in Renal Atherosclerotic Lesions) trial, which enrolled 931 patients with ARAS, there were no differences in primary outcomes including major cardiovascular events (myocardial infarction, stroke, hospitalization was more frequent than in the patients with primary hypertension.…”
Section: Atherosclerotic Renal Artery Stenosis Renal Revascularizatio...mentioning
confidence: 99%
“…27 In the ASTRAL (Angioplasty and Stenting for Renal Artery Lesions) trial, comparing medical therapy with stenting for ARAS in randomly assigned 806 patients, there was no difference in the pre -established outcomes of renal function decline, renal events, cardiovascular events, or death. 27,28 Also, in the CORAL (Cardiovascular Outcomes in Renal Atherosclerotic Lesions) trial, which enrolled 931 patients with ARAS, there were no differences in primary outcomes including major cardiovascular events (myocardial infarction, stroke, hospitalization was more frequent than in the patients with primary hypertension. 21 The study of Wright et al 19 also showed that the patients with ARAS and CKD were characterized by higher prevalence of LV diastolic dysfunction (40.5% vs 12.0%) than individuals with other causes of CKD (control group).…”
Section: Atherosclerotic Renal Artery Stenosis Renal Revascularizatio...mentioning
confidence: 99%
See 3 more Smart Citations